The Effect of Talent Management Practices on Employee Retention: An Empirical Case Study of Wallaga University, Ethiopia - Gudata Abara Chali (Buletin Edukasi Indonesia, 2026)
This study investigates the influence of talent management practices—specifically talent planning, engagement, development, and audits—on employee retention at Wallaga University, a prominent institution within the East Wollega Zone of Oromia, Ethiopia. In the competitive landscape of higher education, retaining skilled academic staff is vital for institutional stability and research excellence. Utilizing a mixed-methods approach, data were gathered from 293 academic staff members via structured questionnaires and interviews. Descriptive statistics indicated a moderate satisfaction level with current recruitment and development strategies, while inferential analysis revealed that talent development is the strongest predictor of retention (β= 0.575, p < 0.001). The regression model explained 65.6% of the variance in employee retention. Findings suggest that while the university has established formal HR structures, improvements in communication and the consistency of talent audits are required to mitigate turnover. The study concludes that institutionalized meritocracy and personalized career pathways are essential for long-term staff commitment in the regional administrative context.